2009
DOI: 10.1167/iovs.08-1843
|View full text |Cite
|
Sign up to set email alerts
|

The Interblink Interval I: The Relationship between Sensation Intensity and Tear Film Disruption

Abstract: The method provides novel information about the development of ocular sensation during ocular surface drying. As evidenced by the complex functions required to adequately describe the relationships, tear film drying and ocular surface sensations are associated in complex ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…The differences between groups reached statistical significance (Mann-Whitney U test, P < 0.05) for ''irritation'' and ''pricking.'' These results agree with our previous studies, which indicate that TBU in eye opening trials was associated with irritation, stinging, and burning, 15,20,22 but also suggest that diminishing corneal fluorescence over time without TBU is associated with an irritative affective response. The difference in discomfort experienced by subjects in the BU and BUmin groups is illustrated in Figures 2 and 3, which show individual data for the change in discomfort during trials reported by four of the subjects in this study.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The differences between groups reached statistical significance (Mann-Whitney U test, P < 0.05) for ''irritation'' and ''pricking.'' These results agree with our previous studies, which indicate that TBU in eye opening trials was associated with irritation, stinging, and burning, 15,20,22 but also suggest that diminishing corneal fluorescence over time without TBU is associated with an irritative affective response. The difference in discomfort experienced by subjects in the BU and BUmin groups is illustrated in Figures 2 and 3, which show individual data for the change in discomfort during trials reported by four of the subjects in this study.…”
Section: Resultssupporting
confidence: 93%
“…Both groups showed increasing discomfort as the median PI decreased, but the BUmin group progressed at a slower rate than the BU group. These data strongly support the hypothesis that the rate of increasing discomfort during extended eye opening trials 22 is highly correlated with the rate of diminishing fluorescence, whether associated with TBU or not.…”
Section: Sensory Measuressupporting
confidence: 85%
See 2 more Smart Citations
“…16 Blinking is driven to a certain extent by ocular surface stimuli. 17 The nonYsoft lensYwearing cornea, which was exposed during a period of consciously not blinking, was found to become irritated with shorter tear breakup time associated with more rapid rates of increased irritation. 17 Innocuous ''cold'' corneal thermoreceptors are activated by drying of the ocular surface and hyperosmotic solutions, conditions which are consistent with a role in tear production.…”
Section: Causes Of Symptomsmentioning
confidence: 99%